ANALISIS KELAYAKAN FINANSIAL USAHA KERIPIK TALAS (STUDI KASUS : PADA INDUSTRI RUMAH TANGGA KUB MENGGAKA DI DESA PORAME KECAMATAN KINOVARO KABUPATEN SIGI) - Asri, Winda Pratiwi; Mapatoba, Marhawati; Tangkesalu, Dance (AGROTEKBIS, 2019)
The purpose of this study is to analyze financial feasibility and conducting business planning Taro Chips Enterprises. The research was conducted at the home industries KUB "Menggaka" which took place in the village of Porame, District Konivaro, Sigi in May to July 2016. The data used in this study using two types of data, primary data and secondary data. Analysis of the data used is the Net Present Value (NPV), Net Benevit Cost Ratio (Net B / C), Internal Rate of Return (IRR), and Payback Period (PP). Results of the analysis showed that the Net Present Value (NPV) of Rp. 53,652,956 and Rp.33,914,761for data input. This indicates that the positive NPV (NPV> 0), so declared eligible to run. Net Benefit Cost Ratio (Net B / C) obtained a value of 5.2 > 1 and 1.215> 1 for data input. Meaning Net B / C is greater than 1 (one), so that the business is feasible to run. Internal Rate of Return (IRR) obtained amounted to 51 percent and 18,95percent for data input. That is, the industry is eligible to run because the rate of return greater than the interest rate applicable (i = 15%) and (i = 18%), while the result of the calculation Payback Period obtained has a repayment period of 1 year 6 months 10 days and 1 years 5 months 14 days to prediction data. That is, in this period of investment costs incurred will be back, so the faster the payback period of investment costs, the business run better.